Workshop report: Schistosomiasis vaccine clinical development and product characteristics. Issue 8 (17th February 2016) - Mo, Annie X.; Colley, Daniel G.
Abstract: A schistosomiasis vaccine meeting was organized to evaluate the utility of a vaccine in public health programs, to discuss clinical development paths, and to define basic product characteristics for desirable vaccines to be used in the context of schistosomiasis control and elimination programs. It was concluded that clinical evaluation of a schistosomiasis vaccine is feasible with appropriate trial design and tools. Some basic Preferred Product Characteristics (PPC) for a human schistosomiasis vaccine and for a veterinary vaccine for bovine use were also proposed.